Пралісові екосистеми Чорногори (у межах Карпатського НПП): сучасний стан, шляхи використання і збереження - Максимюк, Г. В.; Притула, І. М.; Сенчина, Б. В. (Київський національний університет імені Тараса Шевченка, 2017)
Дослідження містить аналіз сучасного стану та проблем збереження пралісів Говерлянського природоохоронного науково дослідного відділення (ПОНДВ). Такі ліси можуть слугувати науковими полігонами. Праліси на території Карпатського національного природного парку (НПП) збереглися у вигляді окремих ділянок чи масивів. Найбільша площа пралісів (квазі-пралісів) у межах Говерлянського ПОНДВ – 774,3 га (17 % від площі лісів), у т.ч. 481,6 га – чисті смерекові; 277,5 га – буково-ялицево-смерекові; 11,9 га – ялицево смерекові та 3,3 га – буково-ялицеві з домішкою смереки. За фондовими матеріалами та польовими маршрутами складена картосхема поширення старовікових лісів. Найбільшого впливу зазнають пралісові ділянки, розміщені на межі з землями інших природокористувачів, та дотичні до територій, де проводиться рекреаційна діяльність. Створення спеціальних еколого – пізнавальних стежок, за межами яких заборонене перебування рекреантів у пралісах, сприятиме мінімізації антропогенного впливу на праліси.

An analysis of the reservation history of Chornohora massif territory of the Carpathian National Nature Park (NNP), as well as the current state and problems of the primeval forests preservation of the Goverla Nature-Oriented Science and Research Department (NOSRD) is included in the research. Such forests can act as scientific polygons. They are examples and, at the same time, models of ecosystems that, to the best of their ability, counteract natural disasters and the effects of anthropogenic influences and global climate change on forest ecosystems. Primeval forests on the territory of the Carpathian NNP have been preserved as separate plots or arrays in size from 0.4 to 228.5 hectares. The total area of old-growth forests and primeval forests of the NNP is 3325.8 hectares, which is only 8.91 % of the forest area. Most of them were preserved as high-altitude spruce (55 %), polydominant spruce (20 %), fir (15 %), beech (5 %), dwarf mountain pine and rare pine (about 5 %) types of forest. The largest area of primeval forests (quasi-primeval forests) is preserved within the limits of the Goverla NOSRD – 774.3 hectares (17 % of the forest area), including 481.6 hectares – pure spruce; 277.5 hectares – beech-fir-spruce; 11.9 hectares – fir-spruce and 3.3 hectares – beech-fir with an addition of spruce. Map of the distribution of old-growth forests is compiled according to stock materials and field researches. The main anthropogenic impact is on primeval areas, located on the border with the lands of other nature users, and lands tangential to the territories where recreational activities are carried out. Creation of special ecological cognitive paths in primeval forests, outside of which stay of tourists is forbidden, will help minimize anthropogenic impact on primeval forests.
Chornohora primeval forests ecosystems (within the Carpathian NNP): current state, ways of use and conservation
Keywords: праліси; квазі-праліси; старовірові ліси; Карпатський національний природний парк; Говерлянське природоохоронне науково-дослідне відділення; primeval forests; quasi-primeval forests; old-growth forests; Carpathian National Nature Park; Goverla Nature-Oriented Science and Research Department